Metal–Organic Frameworks Containing Missing‐Linker Defects Leading to High Hydroxide‐Ion Conductivity. Issue 5 (8th December 2015) - Montoro, Carmen; Ocón, Pilar; Zamora, Félix; Navarro, Jorge A. R.
Abstract: The ionic conductivity properties of the face‐centered cubic [Ni8 (OH)4 (H2 O)2 (BDP_X)6 ] (H2 BDP_X=1, 4‐bis(pyrazol‐4‐yl)benzene‐4‐X with X=H (1 ), OH (2 ), NH2 (3 )) metal–organic framework (MOF) systems as well as their post‐synthetically modified materials K[Ni8 (OH)5 (EtO)(BDP_X)5.5 ] (1@KOH, 3@KOH ) and K3 [Ni8 (OH)3 (EtO)(BDP_O)5 ] (2@KOH ), which contain missing‐linker defects, have been studied by variable temperature AC impedance spectroscopy. It should be noted that these modified materials exhibit up to four orders of magnitude increase in conductivity ‐ values in comparison to pristine1 –3 systems. As an example, the conductivity value of 5.86×10 −9 S cm −1 (activation energy E a of 0.60 eV) for2 at 313 K and 22 % relative humidity (RH) increases up to 2.75×10 −5 S cm −1 ( E a of 0.40 eV) for2@KOH . Moreover, a further increase of conductivity values up to 1.16×10 −2 S cm −1 and diminution of E a down to 0.20 eV is achieved at 100 % RH for2@KOH . The increased porosity, basicity and hydrophilicity of the1@KOH –3@KOH materials compared to the pristine1 –3 systems should explain the better performance of the KOH‐modified materials. Abstract : The missing link : The deliberate introduction of defects onfcu frameworks by KOH/EtOH, leading to missing‐linker defects and metal cluster basification, is responsible for a boosting of the ion conductivity and depletion of activation energy.